Interactions among genes, tumor biology and the environment in cancer health disparities: examining the evidence on a national and global scale - Wallace, Tiffany A. (Oxford University Press, 2011)
Cancer incidence and mortality rates show great variations across nations and between population groups. These variations are largely explained by differences in age distribution, diet and lifestyle, access to health care, cultural barriers and exposure to carcinogens and pathogens. Cancers caused by infections are significantly more common in developing than developed countries, and they overproportionally affect immigrant populations in the USA and other countries. The global pattern of cancer is not stagnant. Instead, it is dynamic because of fluctuations in the age distribution of populations, improvements in cancer prevention and early detection in affluent countries and rapid changes in diet and lifestyle in parts of the world. For example, increased smoking rates have caused tobacco-induced cancers to rise in various Asian countries, whereas reduced smoking rates have caused these cancers to plateau or even begin to decline in Western Europe and North America. Some population groups experience a disproportionally high cancer burden. In the USA and the Caribbean, cancer incidence and mortality rates are excessively high in populations of African ancestry when compared with other population groups. The causes of this disparity are multifaceted and may include tumor biological and genetic factors and their interaction with the environment. In this review, we will discuss the magnitude and causes of global cancer health disparities and will, with a focus on African-Americans and selected cancer sites, evaluate the evidence that genetic and tumor biological factors contribute to existing cancer incidence and outcome differences among population groups in the USA.